Analisa pengaruh fraksi massa penguat sio2 terhadap kekuatan impak dan struktur mikro pada komposit matrik aluminium menggunakan metode stir casting - Grahardian Adi Kusumo; Purwadi Joko Widodo; Wahyu Purwo Raharjo (Jurnal Teknik Mesin Indonesia, 2016)
AMC (Aluminium Matrix Composite) using stir casting method is one of the best way to get superior material. This research is to find out the mass fraction influence of reinforcement SiO2 to impact strength and micro structure on aluminium matrix composite. On this research, mass fraction of reinforcement varied between 3%, 6% and 9%. The making of composite use stir casting method. Specimen test is using optics microsope and impact charpy testing machine. The result of research show that increasing SiO2 can increase the impact strength. The highest impact strength happened at specimen 9% mass fraction of SiO2 (0,363 J/mm2). Observation of micro structur show good bonding between reinforcement and matrix on composite.